COVID-19 AdenoviralVector Vaccine and Central Retinal Vein Occlusion. (4th July 2022) - Romano, Davide; Morescalchi, Francesco; Romano, Vito; Semeraro, Francesco
ABSTRACT: Purpose: The purpose of this article is to report a case of sudden onset ischemic retinal central vein occlusion after a second dose of COVID-19 adenoviral vector vaccine. Case report/observations: A 54-year-old woman with systemic arterial hypertension developed ischemic central retinal vein occlusion in her right eye on day 2 after the second dose of COVID-19 adenoviral vector vaccine ChAdOx1 nCoV-19/ AZD1222, Oxford-AstraZeneca. Conclusion: Adenoviral vector vaccine promotes both cellular and humoral immune responses, increasing the level of inflammatory cytokines. These cytokines are the same implied in the possible pathogenesis of central retinal vein occlusion. Subsequently, we recommend informing patients at risk of possible ocular adverse events, which require urgent evaluation.